2022
DOI: 10.1017/ice.2022.210
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Clostridioides difficile infection rates in Canadian hospitals during the coronavirus disease 2019 (COVID-19) pandemic

Abstract: The COVID-19 pandemic has placed significant burden on healthcare systems. We compared Clostridioides difficile infection (CDI) epidemiology before and during the pandemic across 71 hospitals participating in the Canadian Nosocomial Infection Surveillance System. Using an interrupted time series analysis, we showed that CDI rates significantly increased during the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…On the other hand, multiple other studies showed an increase in CDI rates [2,3,7]. A recent large Canadian study involving multiple centers revealed an 11% increase in hospital-acquired CDI during the pandemic [8].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, multiple other studies showed an increase in CDI rates [2,3,7]. A recent large Canadian study involving multiple centers revealed an 11% increase in hospital-acquired CDI during the pandemic [8].…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, multiple other studies showed an increase in CDI rates [ 2 , 3 , 7 ]. A recent large Canadian study involving multiple centers revealed an 11% increase in hospital-acquired CDI during the pandemic [ 8 ]. Another retrospective analysis, investigating the COVID-19 era until January 2021, identified higher CDI rates during COVID-19 peak periods [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HA-CDI rates did not change in the US hospitals [ 23 ] or even decreased in some EU countries [ 24 , 25 ]. In contrast, the incidence rates of HA-CDIs increased in hospitals participating in the Canadian Nosocomial Infection Surveillance Program [ 26 ], after a period of steady decline before the pandemic. This can be explained by altered or even weakened infection prevention and control practices due to pandemic surge pressures and increased antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of CDI was estimated to have decreased by 24% from 2011 to 2017 when correcting for changes in diagnostics between those years [8]. More recently, the impact of the COVID-19 pandemic on CDI prevalence has been a focus for several studies; while some have noted increased [12,13] or stable prevalence/incidence [14,15], most have demonstrated a decline [16][17][18] corresponding with decreased testing and extraordinary reinforcement of infection prevention measures [15,18,19]. Broader, more definitive data from the CDC would be helpful to best answer the impact the COVID-19 pandemic had on CDI incidence.…”
Section: The Changing Epidemiology Of CDImentioning
confidence: 99%